Initial Performance of Tissue Culture Raised Bamboos in Rajasthan and Gujarat - Srivastava, R. L.; Kumar, Ashok; Sharma, S. K.; Emmanuel, C. J. S. K.; Tomar, U. K. (Indian Forester, 2008)
Keeping in view the low productivity of forestry plantations in Rajasthan and Gujarat, an effort has been initiated to enhance the productivity of bamboo plantations using improved planting material raised either through clonal methods or through tissue culture. These trials have been established at Chakhalia, Jhalod (Gujarat); Kushalgarh (Rajasthan). In total 50 ha area has been covered under these specialty plantations, the bamboo species considered for planting are Dendrocalamus strictus and Bambusa bambos. In these performance trials some experimentation were also laid out to see the effect of soil amelioration using organic and inorganic manures and effect of spacing on the growth and productivity of the bamboo plantations. The spacing used are 5m Ã— 5m and 6m Ã— 6m. The initial establishment's results are quite encouraging in both the states. In Gujarat survival percentage ranges from 97.2 % to 100.0% for both the species whereas in Rajasthan sites it was 67.6% to 96.8% (Kushalgarh). The differences observed in the survival percentage may be due to altitudinal variations as the altitude of Gujarat site is 259 m amsl whereas it was 457.20 m amsl for Rajasthan sites. The overall growth performance of both the species is quite satisfactory. Initial inferences can be drawn from these trials is that bamboos can be introduced in both the states in Agroforestry systems.